Mental and physical attributes defining world-class Norwegian athletes: Content analysis of interviews - Boes, R.; Harung, H. S.; Travis, F.; Pensgaard, A. M. (Scandinavian Journal of Medicine & Science in Sports, 2014)
This study reports the results of a content analysis of interviews with 28 Norwegian world-class athletes and 28 controls, matched for gender, age, and type of sport. Semi-structured interviews explored their perceptions of their best performance. The interviews were analyzed using the ATLAS.ti and yielded 20 higher-order codes. Nine higher-order codes were categorized as inner-oriented, five were categorized as outer-oriented, and six were a combination of inner- and outer-oriented. Statistical analysis, using the Mann-Whitney test, showed significant group differences for seven higher-order codes: (a) two outer-oriented codes relating to "mastery - achievements" and "training - outer"; and (b) five inner-oriented codes relating to "mental preparation," "self-reliance," "training - inner," "wholeness," "performance - inner," and "growth orientation." These findings highlight the importance of both inner- and outer-oriented development for high-level achievement in sports - the "mental game" is as important as the physical game, both during training and competitions. Previously published quantitative data reported higher levels of brain integration, faster habitation to a loud tone, and higher ego and moral development in these world-class athletes. These findings are interpreted in light of a Unified Theory of Performance, which proposes that higher mind-brain development provides a basis for higher performance in any activity.